A hermenêutica fenomenológica na obra inicial de Heidegger - Onate, Neusa Maria Rudek (2018)
The objective of this work is to analyze how a phenomenological investigation is possible in Heidegger, which implies a questioning about the anteriority of matter and the sensitive content of which the world itself is constituted. For Heidegger, the world can not be understood by all its objects, for they do not make up the world, but only from the world do objects come to be. As a parameter of this analysis, we will adopt a conceptual and argumentative line of passages present in the selected set of the initial texts of the philosopher's work, contemplating, above all, the lessons of Marburg. From which we will argue that phenomenology is that of a philosophical inquiry which, in turn, is only possible through a direct and free access, is, for Heidegger, the hermeneutics of fatigue. In developing hermeneutics as a phenomenological method, Heidegger establishes the Abbau by confronting the conceptual problems inherent in the history of philosophy itself. In this conjecture, we intend to point out the philosopher's confrontation with the methodological problems of Husserl's phenomenology through Heidegger's critical analyzes of Logical Investigations and Ideas I. The research aims to present fundamental elements to understand the trajectory of Heidegger's philosophical project in which refers to the critical appropriation of phenomenological concepts.To this end, the general objective of the present research is: 1) To expose the central aspects that make up and make possible an original description of the structural scope, therefore, of hermeneutics as a phenomenological method. 2) Analyze how this investigative method can be considered a free and direct access to describe such structures. 3) To evaluate how Husserl's phenomenology makes hermeneutic phenomenology feasible.